LinkedIn-Based Personal Branding Training To Improve Final Student Career Readiness - Rachmat Tullah; Muktar Muktar; Irwansyah Suwahyu; Muhammad Iqbal; Aghnia Zahrah (PT. Riset Mandiri Nusantara, 2026)
Worker recruitment patterns and career development are now greatly influenced by the development of digital technology. Therefore, it is necessary to develop abilities and skills in final year students as an effort to build a professional image starting from college until after they graduate. At this time, there are still many final year students who do not understand the concept of personal branding and have not utilized the LinkedIn digital platform website optimally as the main means of their career development. This community service activity aims to increase participants' understanding of the importance of personal branding and their ability to manage the LinkedIn website as a means of providing a professional image to support their careers in the future. The service method applied has 4 stages, namely: 1. Preparation stage, 2. Discussion stage, 3. Practice/mentoring stage and 4. Evaluation stage. This activity will be carried out in June 2026 with the target of service being final year students. The results of the service showed that at first, the final year students did not understand the theme of personal branding and the use of LinkedIn. After the service was carried out, participants experienced an increase in knowledge and understanding of the importance of personal branding in supporting their careers in the future. Not only that, but participants are also able to optimize LinkedIn profiles to support their professional image displayed on the LinkedIn website. This is evidenced by compiling profiles, abouts, and other identities filled in on the LinkedIn website. At the end of this activity, an evaluation of the activity was carried out. Evaluations were carried out with participants who participated in this series of activities. The results of the evaluation show that there is a change in the mindset and thinking pattern of participants who now consider personal branding on the LinkedIn website important, so that this will affect their future decisions to improve their professional image through relevant activities.